Audit Sistem Informasi Aplikasi Absensi pada PT. ZMenggunakan Framework COBIT 5.0 - Marup, Akmal (Indonesian Accounting Research Journal, 2024)
The advancement of information technology in the era of globalization has played a crucial role in supporting the sustainability of the business world. One significant aspect is the implementation of attendance-related information systems in human resource management within a company. Attendance serves as a representation of presence, reflecting not only individual participation but also indicating the quality and quantity of work outcomes. This research involves PT. Z, which has adopted an attendance information system to enhance efficiency and reduce reliance on paper-based procedures. The study evaluates information governance using the COBIT 5.0 framework to ensure the transparent implementation of the attendance information system, aligned with established security and information management standards. The research includes an analysis of maturity level results for the MEA.01, DSS.01, and DSS.02 domains, yielding scores of 3.25, 3.083, and 2.77, respectively, with a rounded gap of 1 point from the target level 4. All domains exhibit a similar maturity model, namely the Established Process. Despite achieving satisfactory performance levels, the recommendations emphasize the need to strengthen oversight in the attendance process to enhance the already commendable performance.